Deactivation of pacemaker: Ethical approach or managerial failure? - Marie Macková; Igor Kotlán (DANUBE: Law, Economics and Social Issues Review, 2017)
The decision about the deactivation of a pacemaker must be the result of a multicriteria decision-making process where the legal, ethical and effectiveness aspects must be taken into account and delicately balanced, while also considering the risk of managerial failure. Academic as well as professional discussion is necessary because there is a whole range of question marks on this topic and all the aspects mentioned above. The aim of this paper is to contribute to the debate by presenting the views of Czech physicians about the possibility of deactivation of the pacemaker in patients in terminal states. Based on the results of our research, the following steps are recommended to enable the deactivation of pacemakers in the Czech environment. Before the patient's own indication of pacemaker therapy, treatment should be discussed with the patient in detail, including complications and deactivation options. Czech ethical consultant services should be set up in Czech hospitals. And last but not least, they should take an opinion on this issue as well as the professional society.
Keywords: 330; Deactivation of Pacemaker; Social Care; Ethical Management; Management in Social Sector